Przedsiębiorstwo agrobiznesu w nowych warunkach gospodarowania - Dubicka, Danuta; Orłowska, Maria Jolanta (The Agribusiness Company in New Conditions of Farming, 2006)
The value of agribusiness company is established using the profitable method. In conditions of market economy the farming unit is the welfare which value on financial advantages depends and which it can produce in future periods.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 194-201